Case report: Malignant melanoma of the lower limb with gastric metastasis - Hu, Qiang; Zhou, Fengru; Sun, Yuanshui (Frontiers in Oncology, 2023)
Introduction Malignant melanoma with gastric metastasis is extremely rare. We report a case of gastric metastasis caused by malignant melanoma of the lower limb. Case presentation A 60-year-old woman was hospitalized for left plantar pain. The patient found a black maculopapular eruption on the left sole of her left foot, which caused pain when pressed, and the pain was aggravated by walking, so she went to our hospital for treatment. On the second day of admission, the lesion of the left foot was removed under local anesthesia, and the removed tissue was sent for pathological examination. Combined with immunohistochemistry, it was consistent with malignant melanoma. During hospitalization, the patient developed abdominal pain and asked for gastroscopy. Gastroscopy revealed two 0.5 cm × 0.6 cm spots that can be seen arising from the stomach mucosa which were slightly swollen, slightly black in the center, and without erosion, and no abnormality was found in the other parts. At the same time, a biopsy was taken under a gastroscope and pathology suggests malignant melanoma. The patient could not undergo subsequent treatment due to cost. The patient was followed up until February 2022 and was within the survival period. Conclusion Malignant melanoma gastric metastasis is extremely rare. When a patient has a previous history of melanoma surgery, this needs to be considered when gastrointestinal symptoms are present, and regular endoscopic screening is recommended. Early surgical treatment and postoperative chemotherapy or combined targeted therapy may improve the prognosis of patients.